Kajian Communibiology dalam Komunikasi Keluarga untuk Mendukung Perawatan Penderita Gagal Ginjal Kronis - Putra Fajar, Dewanto; Illahi, Azizun Kurnia (Unitri Press, 2021)
Chronic kidney failure is a degenerative disease that causes the sufferer to experience not only physiological and psychological disorders but also social problems. Interestingly, the social problems experienced by sufferers of chronic kidney failure are likely to increase the physiological and psychological disorders of the sufferer. Therefore, communication to build support for people with chronic kidney failure has a big role to play in increasing self-confidence in people with chronic kidney failure, which indirectly reduces the appearance of physiological and psychological disorders in sufferers of chronic kidney failure. This study seeks to comprehensively describe the aspects of communibiology in the communication process to provide moral support to sufferers of chronic kidney failure. This research is qualitative research using a case study methodological approach and literature review. The literature review is used to provide a detailed explanation of the communibiological processes in individuals and is used to strengthen the researchers' analysis of the observed phenomena. This study provides a big picture that communibiology processes play an important role in the communication processes carried out by families with chronic kidney failure to provide moral support to sufferers, as well as by people with chronic kidney failure to families who provide support, and when sufferers build trust. themselves when facing their social environment. Researchers concluded that moral and spiritual support through family communication has a positive role for chronic kidney failure sufferers to continue treatment and build self-confidence in their social environment. Keywords: family communication; interpersonal communication; communibiology; chronic kidney failure